Measuring School Efficiency: The Contemporary Understanding - Fasasi, Y. A.; Oyeniran, S.; Akinnubi, O. P. (International Journal of Educational Management, 2022)
Evaluation of efficiency of educational unit has become an important priority for many policy makers. A current approach considers the school as a production unit that uses multiple inputs to produce multiple outputs. This paper examines the approaches to measuring efficiency in schools. It critically assesses efficiency from inputs and outputs measures. In the context of the paper approaches to estimating efficiency is classified into two as parametric and non-parametric (regression based) techniques. While the former involves the characterization of the functional forms, the latter makes a linear programming approach to efficiency measurement. Based on this premise, the paper identifies cost and production functions as parametric approach to efficiency measurement while Data Envelopment Analysis (DEA) is identified as a non-parametric approach to estimating school efficiency. The paper recommends the needs for educational administrators and researchers to acquaint themselves with the inputs and outputs of education process for proper management to achieve efficiency and effectiveness in the school system.